1995
DOI: 10.2172/100238
|View full text |Cite
|
Sign up to set email alerts
|

The use of synthetic colloids in tracer transport experiments in saturated rock fractures

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither thle United States Government nor any agency thereof, nor amy of their employees, make any warranty, express or impliedl, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any informationl, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Referencie herein t o any specific commercial product,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 26 publications
(53 reference statements)
1
46
0
Order By: Relevance
“…However, even when fluid in the matrix is completely stagnant, solute can migrate into the matrix via molecular diffusion, resulting in a physical retardation of solute compared to pure fracture transport. This effect has recently been demonstrated on the laboratory scale by Reimus (1995) and on the field scale both by Maloszewski and Zuber (1991) and in the saturated zone at Yucca Mountain by Reimus et al (1999).…”
Section: Matrix Diffusionmentioning
confidence: 76%
“…However, even when fluid in the matrix is completely stagnant, solute can migrate into the matrix via molecular diffusion, resulting in a physical retardation of solute compared to pure fracture transport. This effect has recently been demonstrated on the laboratory scale by Reimus (1995) and on the field scale both by Maloszewski and Zuber (1991) and in the saturated zone at Yucca Mountain by Reimus et al (1999).…”
Section: Matrix Diffusionmentioning
confidence: 76%
“…Also, because of their hydrophilic surfaces, the CML microspheres are relatively stable even at ionic strengths approaching 1 molar (in monovalent cations), which is advantageous when injecting them with ionic solute tracers. CML microspheres behaved more conservatively (less attachment) than silica microspheres and non-modified carboxylated latex microspheres (hydrophobic surfaces) in previous laboratory experiments (Reimus 1995). The use of conservative colloid tracers was expected to result in conservative filtration parameter estimates, which in turn should result in conservative predictions of large-scale colloid transport.…”
Section: Introductionmentioning
confidence: 82%
“…However, values of R c and R n were used such that the nanosensors experience no retardation and the solute tracer does experience retardation. This is based on studies of colloid transport in fractures which showed that nonadsorbing colloids exhibit breakthrough more rapidly than solute tracers because they tend to stay in fluid streamlines and do not experience matrix diffusion (Reimus 1995). Also, the volumetric flow rate q and the masses of the tracer m c and m r were based on values reported by Gentier et al (2010) for the 2005 tracer test performed in the Soultz-sous-Forets reservoir.…”
Section: Example Problemmentioning
confidence: 99%